Design Optimization of CNC Router 2413 for the Interior Design Industry Using Reverse Engineering and DFMA - Chandra Ramadhan; Dewa Kusuma Wijaya; Rudi Tjahyono (Yayasan Inovasi Kemajuan Intelektual, 2025)
The wood industry faces prolonged production times due to the use of conventional tools and the declining number of artisans. This study aims to design the CNC 2413 machine to meet the production needs of the interior design industry by improving efficiency, precision, and adaptability. The design process applies the Reverse Engineering approach combined with Design for Manufacturing and Assembly (DFMA). The key technical aspects include torque calculation, Center of Gravity (CoG) analysis, and assembly mapping. The results indicate that a 3-axis CNC router is sufficient for cutting and engraving tasks, requiring a minimum torque of 0.4116 N·m (Y-axis), 0.3528 N·m (X-axis), and 0.0156 N·m (Z-axis), with a spindle torque of 0.159 N·m. The Nema 24 stepper motor and Bosch GKF router were selected as they meet the specified requirements. The CoG analysis produced X = 56.9–63.0 cm, Y = 100.9–127.3 cm, and Z = 3.884 cm, demonstrating structural stability and resistance to vibration. This design is considered feasible and reliable for long-term use. In addition, the study offers practical significance in terms of potential production cost savings through lower power consumption compared to conventional machines and the opportunity to enhance the production capacity of small and medium enterprises (SMEs) in the interior design sector. This research provides a practical reference for developing CNC routers using locally sourced components, aligned with the technical and economic needs of the interior design industry.